The cutting-edge applications and properties of carbon nanotubes in diagnosis and treatment of lung cancer: a review - Abdollahi Boraei, Seyyed Behnam; Kamalinejad, Fateme; Kiaei, Negin (Frontiers in Biomaterials Science, 2025)
Lung cancer, a predominant source of cancer-related mortality, poses considerable obstacles for conventional therapies. Carbon nanotubes, an innovative category of nanomaterials, have surfaced as prospective agents for cancer treatment owing to their distinctive characteristics. This article examines the potential of carbon nanotubes (CNTs) in the treatment of lung cancer, emphasizing their roles in targeted drug delivery, photothermal and photodynamic therapy, and gene therapy. The high surface area, electrical conductivity, and biocompatibility of CNTs render them optimal for the delivery of anticancer medications, thereby augmenting their efficacy and minimizing side effects. Furthermore, CNTs can be employed in photothermal and photodynamic therapy, facilitating cell death via heat production or oxidative stress. Furthermore, carbon nanotubes can effectively transport genetic material for gene therapy, providing a focused method for lung cancer treatment. Despite limitations like as clinical translation, carbon nanotubes exhibit significant potential as novel instruments for enhancing lung cancer therapy outcomes.